Synthesis of New Lathyrane Diterpenoid Derivatives from Euphorbia lathyris and Evaluation of Their Anti‐Inflammatory Activities. Issue 2 (16th January 2020) - Wang, Wang; Wu, Yanli; Li, Chen; Yang, Yueying; Li, Xingzhou; Li, Hua; Chen, Lixia
Abstract: Euphorbia factor L3, a lathyrane diterpenoid extracted from Euphorbia lathyris, was found to display good anti‐inflammatory activity with very low cytotoxicity. To find more potent anti‐inflammatory drugs, two series of Euphorbia factor L3 derivatives with fatty and aromatic acids were designed and synthesized. Among them, lathyrane derivative 5n exhibited most potent inhibition on LPS‐induced NO production in RAW264.7 cells with no obvious cytotoxicity. To determine the key characteristics of Euphorbia factor L3 derivatives that contribute to anti‐inflammatory activity, we conducted a structure‐activity relationship study of these compounds. Abstract :